2023
DOI: 10.1530/etj-22-0175
|View full text |Cite
|
Sign up to set email alerts
|

Multiple overlapping microwave ablation in benign thyroid nodule: a single-center 24-month study

Abstract: Objective: This study aimed to evaluate the safety and long-term efficacy using the multiple overlapping ablation technique with a novel non-cooled microwave system in benign symptomatic thyroid nodules. Methods: This prospective cohort single-center study collected complication data from the start of the procedure to 30 days postoperatively and evaluated the safety and effectiveness with a follow-up of 24 months. Ultrasound examinations were performed to determine the volume shrinkage during follow-up. Thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…There were no cases of major complications during the study, although one patient (3.3%) suffered from transient aphonia, which resolved after three months. MWA also does not cause the heat theft that is present with RFA [97].…”
Section: Thermal Ablationmentioning
confidence: 95%
“…There were no cases of major complications during the study, although one patient (3.3%) suffered from transient aphonia, which resolved after three months. MWA also does not cause the heat theft that is present with RFA [97].…”
Section: Thermal Ablationmentioning
confidence: 95%
“…Among them, MWA can potentially eradicate larger benign thyroid nodules with larger coagulation areas and is less affected by the heat sink effect caused by vessels around the nodule [8,9]. In recent years, multiple studies have shown that MWA is effective and safe for benign thyroid nodules [10][11][12]. However, due to the degree and speed of nodule volume reduction, which varies from individual to individual, the appropriate treatment options for benign thyroid nodules that cause cosmetic problems remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound-guided percutaneous thermal ablation of thyroid nodules has been widely used in clinical practice because of its obvious advantages and because it is highly effective. [13][14][15] This treatment mainly includes radiofrequency ablation (RFA), microwave ablation (MWA), and laser ablation (LA). The principle of radiofrequency ablation treatment is to use the high-frequency electromagnetic wave generated by the radiofrequency instrument inserted into the thyroid nodule to make the positive and negative ions in the cell move rapidly, causing frictional heating so that the thyroid nodule will produce coagulative necrosis due to high temperature, and then be absorbed and cleared by the body's immune system.…”
Section: Introductionmentioning
confidence: 99%